Degradation of trichloroethylene by double dielectric barrier discharge (DDBD) plasma technology: Performance, product analysis and acute biotoxicity assessment. (July 2023) - Hu, Xu-Rui; Wang, Yong-Chao; Tong, Zhen; Wang, Can; Duan, Er-Hong; Han, Meng-Fei; Hsi, Hsing-Cheng; Deng, Ji-Guang
Abstract: Trichloroethylene is carcinogenic and poorly degraded by microorganisms in the environment. Advanced Oxidation Technology is considered to be an effective treatment technology for TCE degradation. In this study, a double dielectric barrier discharge (DDBD) reactor was established to decompose TCE. The influence of different condition parameters on DDBD treatment of TCE was investigated to determine the appropriate working conditions. The chemical composition and biotoxicity of TCE degradation products were also investigated. Results showed that when SIE was 300 J L −1, the removal efficiency could reach more than 90%. The energy yield could reach 72.99 g kWh −1 at low SIE and gradually decreased with the increase of SIE. The k of the Non-thermal plasma (NTP) treatment of TCE was about 0.01 L J −1 . DDBD degradation products were mainly polychlorinated organic compounds and produced more than 373 mg m −3 ozone. Moreover, a plausible TCE degradation mechanism in the DDBD reactors was proposed. Lastly, the ecological safety and biotoxicity were evaluated, indicating that the generation of chlorinated organic products was the main cause of elevated acute biotoxicity. Graphical abstract: Image 1 Highlights: Effects of some operational conditions on TCE removal by DDBD were evaluated. Energy yield and kinetics of TCE degradation by DDBD were calculated. The possible decomposition pathways of DDBD in this system were proposed. Residual toxicity after DDBD decomposition was significantly increased.